2007
DOI: 10.1038/sj.onc.1210668
|View full text |Cite
|
Sign up to set email alerts
|

Two Epstein–Barr virus (EBV) oncoproteins cooperate to repress expression of the proapoptotic tumour-suppressor Bim: clues to the pathogenesis of Burkitt's lymphoma

Abstract: Epstein-Barr virus (EBV) contributes to the development of several human cancers including the endemic form of Burkitt's lymphoma (BL). In culture, EBV induces the continuous proliferation of primary B cells as lymphoblastoid cell lines (LCLs) and if EBV-negative BL-derived cells are infected with EBV, latency-associated viral factors confer resistance to various inducers of apoptosis. Nuclear proteins EBNA3A and EBNA3C (but not EBNA3B) are necessary to establish LCLs and their expression may be involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(245 citation statements)
references
References 46 publications
5
235
1
2
Order By: Relevance
“…25,26 Homozigous deletion of Bim is associated with mantle cell lymphoma 27 and survival of autoreactive T and B cells, 28,29 and repression of Bim expression by EBV has a significant role in Burkitt lymphoma. 30 Several antitumor chemotherapies were demonstrated to kill neoplastic cells through Bim-activated pathways, including a Raf kinase inhibitor in acute myeloid cells, 31 glucocorticoids in leukaemia cell lines and primary leukemia cells, 32,33 ABT-737 for chronic lymphocytic leukaemia cells and myeloma cell lines 18 and paclitaxel in xenografts of epithelial cancer cells. 34 Altogether, Bim can be classified as a powerful tumour suppressor, and its strong pro-apoptotic activity is regulated both at transcriptional and post-translational levels.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Homozigous deletion of Bim is associated with mantle cell lymphoma 27 and survival of autoreactive T and B cells, 28,29 and repression of Bim expression by EBV has a significant role in Burkitt lymphoma. 30 Several antitumor chemotherapies were demonstrated to kill neoplastic cells through Bim-activated pathways, including a Raf kinase inhibitor in acute myeloid cells, 31 glucocorticoids in leukaemia cell lines and primary leukemia cells, 32,33 ABT-737 for chronic lymphocytic leukaemia cells and myeloma cell lines 18 and paclitaxel in xenografts of epithelial cancer cells. 34 Altogether, Bim can be classified as a powerful tumour suppressor, and its strong pro-apoptotic activity is regulated both at transcriptional and post-translational levels.…”
Section: Introductionmentioning
confidence: 99%
“…EBNA3C or EBNA3A have many specific and potentially significant interactions with other transcription factors or modifiers, including PU.1, Spi-B, HDAC1, DP103, prothymosin-α, p300, Nm23-H1, SUMO1, and SUMO3, cyclin A, SCF SKP2 ubiquitin ligase, pRb, Chk2, Mdm2, and MRS18-2, and these interactions could be relevant to CDKN2A p16 INK4A or p14 ARF regulation and LCL growth (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Furthermore, EBNA3C upregulates TCL1A and ITGA4, down-regulates JAG1 and NCALD RNAs, and cooperates with EBNA3A in repressing Bim, a proapoptotic Bcl-2 family protein (24,(39)(40)(41). Indeed, EBNA3C and EBNA3A may cooperatively repress the p16 INK4A and p14 ARF tumor suppressors to allow cell cycle progression, as is required for MYC conversion of tissue cells to stem cells, for HPV16-and HPV18-induced cervical cancer, and for other enforced cell proliferations (42)(43)(44).…”
mentioning
confidence: 99%
“…Most reports show that BIM is a key regulator of life and death decisions (Anderton et al, 2008;Paschos et al, 2009). Thus, it is not surprising that EBV BHRF1 binds to the BH3-only peptide BIM and interacts strongly with its protein (Flanagan and Letai, 2008).…”
Section: Bhrf1 Binds To Bimmentioning
confidence: 99%
“…Using recombinant EBVs established with a bacterial artificial chromosome (BAC) system, it was revealed that EBNA3A and EBNA3C cooperate to inhibit the activation of the tumor-suppressor gene BIM. The inhibition appears to be predominantly directed at the regulation of BIM mRNA levels (Anderton et al, 2008). This process may involve an epigenetic mechanism that can be initiated or maintained by interactions between EBNA3A and EBNA3C and suppressive marks on local chromatin.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation